Next-Generation Sequencing Analysis of the Within-Host Genetic Diversity of Influenza A(H1N1)pdm09 Viruses in the Upper and Lower Respiratory Tracts of Patients with Severe Influenza - Ikuyo Takayama; Binh Gia Nguyen; Co Xuan Dao; Thach The Pham; Tuan Quoc Dang; Phuong Thai Truong; Thanh Van Do; Thuy Thi Phuong Pham; Seiichiro Fujisaki; Takato Odagiri; Hideki Hasegawa; Noriko Nakajima (mSphere, 2021)
The D222G/N substitution in the hemagglutinin (HA) protein of influenza A(H1N1)pdm09 virus has been reported to be associated with disease severity and mortality in numerous previous studies. In the present study, 75% of lower respiratory samples contained heterogeneous influenza populations that carried different amino acids at position 222 of the HA protein, whereas all upper respiratory samples only contained the wild-type 222D.